• Предмет: Алгебра
  • Автор: katywell273
  • Вопрос задан 7 лет назад

Помогите, пожалуйста, решить. СРОЧНО!!

Приложения:

Ответы

Ответ дал: NNNLLL54
0
1); ; f(x)=x^5+3x^4-10x+4\\f'(x)=5x^4+3cdot 4x^3-10=5x^4+12x^3-10\\2); ; f(x)= sqrt[5]{x^2}+frac{9}{sqrt{x}}\\f'(x)=frac{2}{5}cdot x^{frac{2}{5}-1}+9cdot (-frac{1}{2})cdot x^{-frac{1}{2}-1}=frac{2}{3}cdot x^{-frac{3}{5}}-frac{9}{2}cdot x^{-frac{3}{2}}=\\=frac{2}{5sqrt[5]{x^3}}-frac{9}{2sqrt{x^{3}}}\\3); ; f(x)=cos^2x+(sinx)^{-1}\\f'(x)=2, cosxcdot (cosx)'-(sinx)^{-2}cdot (sinx)'=\\=2, cosxcdot (-sinx)-(sinx)^{-2}cdot cosx=-sin2x-frac{cosx}{sin^2x}

4); ; f(x)=e^{3x-1}\\f'(x)=e^{3x-1}cdot (3x-1)'=e^{3x-1}cdot 3\\5); ; f(x)=8x^2-x^4\\f'(x)=8cdot (x^2)'-(x^4)'=8cdot 2x-4x^3=16x-4x^3
Вас заинтересует